The Change of HRV before, during and after Tai Chi-XuLingDingJin - Fu, Jiahao; Liu, Zhenghu (The Journal of the International Society of Chinese Health Practices, 2021)
XuLingDingJin (XLDJ) is a very important movement key in Tai Chi practice; It pays attention to the posture of the external head and trunk, the concentration of internal consciousness and nerves, and connects the inside and outside with breathing luck to form a whole, so as to achieve the cultivation state of "rising clear Qi, sinking turbid Qi, full middle Qi and unity of heaven and man". Tai Chi practice pays attention to the three levels of Xin, Qi and Yi, but how to use Yi and practice Yi can not be scientifically and objectively explained. From a physiological point of view, Yi is the excited state of the cerebral cortex and the coordination and unity with the whole body. XLDJ can well activate the function of the nervous system by stimulating the cerebral cortex, so as to improve human function. However, how to objectively demonstrate that XLDJ of Tai Chi has a good stimulating effect on the nervous system is the core problem of this study. Objective: To explore the changes of HRV before, during and after Tai Chi-XLDJ, determine the changes of heart rate and autonomic nerve of young practitioners in the state of rest, XLDJ and recovery, and explore the exercise value of Tai Chi on human function. Methods: 25 college students were selected as subjects to test and analyze the time domain, frequency domain and nonlinear indexes of heart rate and HRV before, during and after Tai Chi-XLDJ. Results: 1) the heart rate of the subjects increased significantly during XLDJ and decreased significantly after exercise. The HRV time domain indexes nn50 and pNN50 decreased significantly during exercise and increased significantly after exercise; RMSSD decreased during exercise and increased after exercise; On the contrary, SDNN increased during exercise and decreased after exercise. 2) The frequency domain index VLF increased during exercise and decreased after exercise; LF and TP increased significantly during exercise and decreased significantly after exercise; LF/HF increased during exercise and decreased after exercise; On the contrary, HF decreased significantly during exercise and increased significantly after exercise. 3) The nonlinear index SD1 decreased during exercise and increased after exercise; SD2 increased during exercise and decreased after exercise; SD2/SD1 increased during exercise and decreased after exercise; But the nonlinear indexes SD1, SD2 and SD2/SD1 had no significant change. Conclusion: An acute 5-minute Tai Chi-XLDJ exercise can effectively stimulate the autonomic nerve and improve the autonomic regulation ability of the subject's nervous system, so as to improve human function. During the exercise, the HRV of the subjects decreased and gradually recovered after exercise. The central sympathetic nerve activity strengthened during exercise and the parasympathetic nerve activity weakened during exercise. Both recovered and tended to balance after exercise.